Optimization of Literacy, Numeracy, and Technology Adaptation through the Implementation of the Kampus Mengajar Program - Sinta Ulina Situmorang (PT. Mifandi Mandiri Digital, 2024)
Improving literacy and numeracy at the primary education level is a crucial aspect that must be prioritized in the context of national educational development. One of the initiatives to enhance students' literacy and numeracy skills in Indonesia is the